EDUCATIONAL ADVANCEMENTS IN THE DIGITAL EPOCH: A MULTIFACETED EXPLORATION OF THE STRATEGIC INCORPORATION OF TECHNOLOGY TO AMPLIFYEDUCATIONAL QUALITY AND LEARNING OUTCOMES IN PRIMARY EDUCATION ACROSS INDONESIA - Iswan Riyadi; Sitti Nur Alam; Cut Ita Erliana; Dahlan Abdullah; Al-Amin (Adisam Publisher, 2023)
Amid the digital era, this research embarked on a comprehensive exploration of the strategic Integration of technology in primary education within the diverse educational landscape of Indonesia. The study delved into the multifaceted dynamics of technology's role in amplifying the quality of education and enhancing learning outcomes. The research unveiled a rich tapestry of findings, elucidating the promises and challenges associated with technology integration. It unearthed a positive correlation between technology integration and improved learning outcomes, where students in schools with higher technology integration consistently achieved better results in standardized assessments. However, the study also illuminated the striking disparities in technology integration, with urban schools benefiting from more advanced technological infrastructure than their rural counterparts. The implications of this research reverberate throughout the Indonesian educational landscape, emphasizing the imperative to bridge the digital divide and ensure equitable access to technology. As the digital epoch continues to reshape educational paradigms, this study stands as a testament to the transformative potential of technology when harnessed strategically and responsibly, with an unwavering focus on enhancing educational quality and empowering the next generation of learners.